Resin catalyst, preparation method thereof and application of resin catalyst in bisphenol A synthesis
By grafting perfluoroalkylsulfonyl and sulfonate on a macroporous crosslinked polystyrene microsphere support and forming ionic bonds with sulfhydryl alkylamine, the hydrophilicity of the resin catalyst is regulated, and the hydrophilicity of the catalyst is solved. The problem of reaction hindering is achieved, and the efficient and stable catalytic effect in bisphenol A synthesis is achieved.
Patent Information
- Application Number
- CN202411568988.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
In the existing bisphenol A production process, the hydrophilicity of the catalyst causes water molecules to occupy the active site, hinder the reaction process, and the catalyst is inefficient in use and poor stability.
Large pore crosslinked polystyrene microspheres are used as support, and perfluoroalkylsulfonyl and sulfonate are grafted thereon. By forming ionic bonds with sulfhydryl alkylamines, the hydrophilicity of the resin catalyst is regulated and catalytic activity is improved. and stability.
The high activity and excellent stability of the catalyst in bisphenol A synthesis are achieved, the problem of water molecules occupying active sites is overcome, and the reaction efficiency and product purity are improved.
Smart Images

Figure CN119425791A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical industry, and in particular to a resin catalyst and a preparation method thereof and application thereof in the synthesis of bisphenol A. Background Art
[0002] Bisphenol A [also known as 2,2-bis(4-hydroxyphenyl)propane] is an important chemical raw material. Its main use is in the production of polycarbonate, epoxy resin, polysulfone resin, polyphenylene ether resin, unsaturated polyester resin and other polymer materials. It also plays an important role in the production of fine chemical products - plasticizers, flame retardants, antioxidants, rubber antioxidants, pesticides, coatings and dyes.
[0003] Bisphenol A is usually prepared by condensing phenol and acetone in the presence of an acid catalyst. In the early production process of bisphenol A, commonly used catalysts included inorganic acids such as hydrogen chloride and sulfuric acid. Among them, the catalyst used in the hydrogen chloride method is anhydrous hydrogen chloride, which has a high reaction selectivity and can produce bisphenol A products of good quality. Therefore, this process is more commonly used in industry. However, the disadvantage of this method is that hydrogen chloride is extremely corrosive, which imposes strict requirements on the material selection of pipelines and equipment, resulting in the gradual elimination of this process. The sulfuric acid method uses 75% to 80% sulfuric acid. Although it can produce bisphenol A, its product is darker in color and lower in purity. At the same time, the material consumption is large, and a large amount of phenol-containing and acid-containing wastewater and waste acid are generated during the production process, causing serious pollution to the environment and gradually being eliminated (Meng Jian. Chemical Engineering Design Communications, 2021, 47(02):140-141.). Due to the many shortcomings of the hydrogen chloride method and the sulfuric acid method catalytic technology, researchers have developed a variety of heterogeneous catalysts to achieve clean production of bisphenol A. For example, the sulfonic acid functionalized mesoporous MCM-41 molecular sieve prepared by Debasish Das (Das D.al., Chemical Communications, 2001 (21): 2178-2179) catalyzes the condensation of phenol and acetone to synthesize bisphenol A at a relatively low temperature with high selectivity. Chen Qun (Chen Qun et al. CN 1544152A, 2003) introduced F into a resin modified with mercaptoalkylamine. - , Cl - Br - 、NO 3 -Or electron-withdrawing groups such as C=O, it is found that the heat resistance of this resin is significantly improved, the degradation rate of sulfonic acid groups is reduced, the utilization rate of active centers is high, and the catalyst channels are not easily blocked. The needs of bisphenol A production - catalytic activity, selectivity and life can be met. Krystyna (Krystyna Nowinska.al., Applied Catalysis A, 2000, 203: 91-100) studied the acid cesium / ammonium salt heteropolyacid catalyst supported by mesoporous molecular sieve MCM-41, and fixed the heteropolyacid atoms in the interior of the mesoporous molecular sieve MCM-41 by the Soled method so that the catalyst catalytic synthesis of bisphenol A yield is stable. There are various types of heterogeneous catalysts for catalytic synthesis of bisphenol A, but strongly acidic ion exchange resins are widely used in large-scale production because of their high reactivity and good selectivity, low production cost, easy separation from reaction products, environmental friendliness, low corrosiveness and other advantages.
[0004] Commonly used strong acid ion exchange resins are sulfonated polystyrene-divinylbenzene copolymers or their modified forms. In order to improve the activity of resin catalysts, people use organic compounds containing mercapto groups as co-catalysts together with ion exchange resins, which greatly increases the reaction rate. For example, Iwahara Masahiro (Iwahara Masahiro et al., CN 1287551A, 1999) greatly increased the yield of bisphenol A by adding alkyl mercaptan to the reaction solution. However, due to the high toxicity, bad smell and complicated subsequent separation of mercapto compounds, they have rarely been used. Now, the mercapto co-catalyst is fixed on the resin catalyst by chemical bonding. For example, Faler (Faler.al., US 4294995, 1981) et al. chlorosulfonated the resin into sulfonyl chloride, then acylated it with bisaminoethyl disulfide, and then reduced it to form a mercaptan-type strong acid resin bonded by SN covalent bonds. The resin catalyzed the synthesis of bisphenol A from phenol and acetone with a selectivity of up to 98%, but the preparation process was complicated, and the ratio of thiol to sulfonic acid group was not easy to control in the optimal state, so it was not widely used. Romeo B Wagner (Romeo B Wagner.al., US 3172916, 1965) acylated some sulfonic acid groups in a strong acid cation exchange resin with chlorosulfonic acid to sulfonyl chloride, and then reduced it to thiophenol with metal tin in concentrated hydrochloric acid, which greatly improved the catalyst activity. However, due to the poor chemical stability of thiophenol, it is very easy to be oxidized, so the life of this type of catalyst is short. Francis NApel (Francis NApel.al., US 3153001, 1964) proposed to graft alkyl mercaptan onto a strongly acidic cation exchange resin by esterification, which showed good catalytic activity at higher temperatures, but the sulfhydryl group connected by the sulfonate structure was easily hydrolyzed and lost, and the stability was poor. He Mingyang (He Mingyang et al. CN 1583269A.2005) used mercaptoalkyl quaternary ammonium salt as a sulfhydrylating agent and modified the base resin by an ion exchange method to obtain a bisphenol A synthesis catalyst. The prepared catalyst has the characteristics of high catalytic activity, good selectivity and long service life, and because of its simple preparation method, it has become the main preparation method of modern bisphenol A catalyst.
[0005] The reaction equipment for producing bisphenol A by resin method mainly adopts fixed bed reaction process. The reactor is generally a fixed bed reactor, in which the catalyst is not easy to wear, has a relatively long service life, is easy to control the residence time, has a simple equipment structure, and has the advantages of stable operation. However, the control of water requires high requirements, because water molecules can easily form hydrogen bonds with the sulfonic acid groups in the resin and occupy the active center of the catalyst, thereby hindering the phenol-acetone condensation reaction. The various cation exchange resin catalysts developed by the above technology have high activity and selectivity. However, these resin catalysts are relatively hydrophilic. In the process of catalyzing the condensation of phenol and acetone to synthesize bisphenol A, the acetone molecules in the raw materials can easily enter the resin catalyst and contact the active sites, but the phenol molecules are difficult to diffuse into and contact the active sites, and the catalyst utilization efficiency is reduced; the byproduct water generated by the product can easily bind to the active sites and is not easy to remove, which reduces the catalytic activity and stability of the catalyst. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a resin catalyst and a preparation method thereof and application in the synthesis of bisphenol A. The present invention uses macroporous cross-linked polystyrene microspheres as carriers, which is not only conducive to the diffusion of acetone and phenol molecules into the resin catalyst and contact with active sites, but also conducive to the diffusion of the generated product bisphenol A; the hydrophilicity and hydrophobicity of the resin catalyst are regulated by regulating the chain length (carbon number, the more carbon numbers, the stronger the hydrophobicity) of the perfluoroalkyl sulfonyl group grafted onto the carrier, so that the water occupying the active sites is easier to remove and the phenol molecules are easier to contact the active sites. The resin catalyst prepared by the present invention not only shows high catalytic activity in catalyzing the condensation of phenol and acetone to synthesize bisphenol A, but also has excellent catalytic stability.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a resin catalyst, comprising the following steps:
[0009] 1) swelling the macroporous cross-linked polystyrene microspheres to obtain swollen microspheres;
[0010] 2) mixing the swollen microspheres obtained in step 1) with fuming sulfuric acid and a sulfonic acid reagent and stirring the mixture to react to obtain a modified resin;
[0011] The sulfonic acid reagent includes one or more of trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, perfluoropropanesulfonic acid and perfluorobutanesulfonic acid;
[0012] 3) Mixing the modified resin obtained in step 2) with N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt, and performing heat treatment under the protection of an inert gas to obtain a resin catalyst.
[0013] Preferably, in step 1), the particle size of the macroporous cross-linked polystyrene microspheres is 800-1000 μm, the pore size is 50-100 nm, and the cross-linking degree is 10-20%;
[0014] The swelling conditions include: mixing the macroporous cross-linked polystyrene microspheres with ethylene dichloride and swelling for 40 minutes;
[0015] The mass ratio of the macroporous cross-linked polystyrene microspheres to the volume ratio of ethylene dichloride is 100 g:500 mL.
[0016] Preferably, in step 2), the mass ratio of fuming sulfuric acid, sulfonic acid reagent and macroporous cross-linked polystyrene microspheres is 6:2:1.
[0017] Preferably, the stirring reaction conditions in step 2) include: temperature of 90° C., time of 12 h, and rotation speed of 300 rpm.
[0018] Preferably, the mass ratio of the modified resin in step 3) to N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt is 100:5.49.
[0019] Preferably, the heat treatment conditions in step 3) include: temperature of 80°C, time of 8h, and rotation speed of 300rpm;
[0020] After the heat treatment, the resin catalyst is obtained by washing and drying in sequence;
[0021] Wash with deionized water until neutral;
[0022] The drying conditions include: a temperature of 80-100° C. and a drying time of 24 hours.
[0023] The present invention also provides a resin catalyst prepared by the preparation method described in the above technical solution, wherein the resin catalyst has active groups, and the active groups include sulfonate, perfluoroalkylsulfonyl and mercaptoalkylamine.
[0024] The present invention also provides application of the resin catalyst described in the above technical solution in the synthesis of bisphenol A.
[0025] Preferably, the application comprises the following steps:
[0026] 1) mixing the resin catalyst with phenol and swelling them to obtain a swollen product;
[0027] The mass ratio of the resin catalyst volume to phenol is 5 mL:40 g;
[0028] The swelling conditions include: stirring at 70° C. for 3 h;
[0029] 2) mixing the swollen product obtained in step 1) with acetone and reacting the mixture to obtain bisphenol A;
[0030] The mass ratio of acetone to phenol is 2.5:40;
[0031] The reaction conditions include: temperature of 70° C. and reaction time of 4 h.
[0032] Preferably, the application comprises the following steps:
[0033] The resin catalyst was loaded into a stainless steel fixed bed reactor, and the phenol-acetone mixture was heated at 70°C at a space velocity of 1 h -1 Carry out continuous reaction to obtain bisphenol A;
[0034] The stainless steel fixed bed reactor has an inner diameter of 30 mm and a length of 200 mm;
[0035] The residence time of the phenol-acetone mixture in the catalyst bed of the stainless steel fixed bed reactor is 1 hour;
[0036] The molar ratio of phenol to acetone in the phenol-acetone mixed solution is 10:1.
[0037] The invention adopts macroporous cross-linked polystyrene microspheres as carriers, grafts sulfonate groups and perfluoroalkylsulfonyl groups onto the carriers, and adsorbs mercaptoalkylamine onto the carriers by forming ionic bonds with sulfonate groups. The prepared resin catalyst overcomes the problem that water molecules are easily bound to active sites and difficult to remove in catalyzing condensation of phenol and acetone to synthesize bisphenol A. The prepared catalyst has high catalytic activity and excellent stability.
[0038] The resin catalyst of the present invention has not only high catalytic activity and selectivity, but also good stability. Among them, the macroporous cross-linked polystyrene microspheres have a large pore size, which is conducive to the diffusion of reactants and products, and are used as a carrier for preparing the resin catalyst. The sulfonate group is grafted on the carrier through a covalent bond to serve as an acid active site. The perfluoroalkyl sulfonyl group is grafted on the carrier through a covalent bond. Because it has a hydrophobic functional group, it serves as a functional group for regulating the hydrophilicity and hydrophobicity of the resin catalyst. The mercaptoalkylamine is adsorbed on the carrier by forming an ionic bond with the sulfonate group, and serves as a cocatalyst for catalyzing the condensation of phenol and acetone to synthesize bisphenol A.
[0039] The present invention utilizes perfluoroalkyl sulfonyl groups grafted onto a resin to change the hydrophilicity and hydrophobicity of the resin, and regulates the hydrophilicity and hydrophobicity of the resin catalyst by regulating the chain length (carbon number) of the perfluoroalkyl sulfonyl groups grafted onto the carrier, so that the resin catalyst has high catalytic activity and strong stability.
[0040] Beneficial effects of the present invention:
[0041] (1) The present invention uses macroporous cross-linked polystyrene microspheres as carriers, which not only facilitates the diffusion of acetone and phenol molecules into the resin catalyst and contact with the active sites, but also facilitates the diffusion of the generated product bisphenol A. The hydrophilicity and hydrophobicity of the resin catalyst are regulated by regulating the chain length (carbon number) of the perfluoroalkyl sulfonyl group grafted onto the carrier, so that the water occupying the active sites is easier to remove and the phenol molecules are easier to contact the active sites. The prepared resin catalyst catalyzes the condensation of phenol and acetone to synthesize bisphenol A, and not only exhibits high catalytic activity, but also has excellent catalytic stability.
[0042] (2) The preparation method of the resin catalyst provided by the present invention has simple steps, low cost, green and pollution-free, high utilization rate of active components, good preparation repeatability, and is combined with a continuous flow fixed bed reactor under mild conditions (70°C, 1h -1 ) has achieved excellent performances of yield ≥85%, bisphenol A (≥95%) selectivity, and stability of ≥120 days. It can achieve separation of catalyst and product, simple production process, high product purity, and greatly reduce production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments are briefly introduced below.
[0044] Figure 1 Schematic diagram of the synthesis of resin catalyst;
[0045] Figure 2 Graphs showing static contact angles of resin catalysts A, B, C, D, E, and F in Example 5;
[0046] Figure 3 This is a stability test data diagram of catalyst C in Example 7;
[0047] Figure 4 This is a graph showing the stability test data of Catalyst E in Comparative Example 2. DETAILED DESCRIPTION
[0048] The present invention provides a method for preparing a resin catalyst, comprising the following steps:
[0049] 1) swelling the macroporous cross-linked polystyrene microspheres to obtain swollen microspheres;
[0050] 2) mixing the swollen microspheres obtained in step 1) with fuming sulfuric acid and a sulfonic acid reagent and stirring the mixture to react to obtain a modified resin;
[0051] The sulfonic acid reagent includes one or more of trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, perfluoropropanesulfonic acid and perfluorobutanesulfonic acid;
[0052] 3) Mixing the modified resin obtained in step 2) with N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt, and performing heat treatment under the protection of an inert gas to obtain a resin catalyst.
[0053] The invention swells macroporous cross-linked polystyrene microspheres to obtain swollen microspheres.
[0054] The present invention uses the conventional method "Synthesis method of macroporous cation exchange resin whose applicant is China Petrochemical Corporation and application number is CN1583269A.2005" to synthesize macroporous cross-linked polystyrene microspheres, which have rich pore structures inside and outside, and can be uniformly grafted with sulfonic acid functional groups, perfluoroalkyl sulfonyl groups and mercaptoalkylamines; during the catalytic reaction, the reactants can reach the inside of the carrier through the porous structure and contact with the active sites to achieve a catalytic condensation reaction. In the present invention, the particle size of the macroporous cross-linked polystyrene microspheres is 800-1000 μm, the pore size is 50-100 nm, and the cross-linking degree is 10%-20%.
[0055] In the present invention, the swelling conditions preferably include: mixing the macroporous cross-linked polystyrene microspheres with ethylene dichloride and then swelling for 40 minutes. In the present invention, the mass ratio of the macroporous cross-linked polystyrene microspheres to the volume ratio of ethylene dichloride is preferably 100 g:500 mL.
[0056] The present invention mixes the obtained swollen microspheres with fuming sulfuric acid and a sulfonic acid reagent and then stirs and reacts to obtain a modified resin. In the present invention, the mass ratio of the fuming sulfuric acid, the sulfonic acid reagent and the macroporous cross-linked polystyrene microspheres is preferably 6:2:1. In the present invention, the sulfonated reagent provides one or more of trifluoromethylsulfonyl, pentafluoroethanesulfonyl, perfluoropropanesulfonyl and perfluorobutanesulfonyl. In the present invention, the stirring reaction conditions preferably include: a temperature of 90°C, a time of 12h, and a rotation speed of 300rpm.
[0057] The present invention mixes the obtained modified resin with N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt, and performs heat treatment under the protection of inert gas to obtain a resin catalyst.
[0058] In the present invention, the N, N, N-trimethyl-3-mercaptopropyl quaternary ammonium salt is derived from SAGECHEM LIMITED, No. 8, Jiashan Road, Hangzhou City, Zhejiang Province, and the CAS number is 14617-77-7. In the present invention, the mass ratio of the modified resin to the N, N, N-trimethyl-3-mercaptopropyl quaternary ammonium salt is preferably 100:5.49. In the present invention, the conditions of the heat treatment preferably include: a temperature of 80°C, a time of 8h, and a speed of 300rpm. In the present invention, after the heat treatment, the resin catalyst is obtained by washing and drying in sequence. The present invention preferably uses deionized water for washing to neutrality. In the present invention, the drying conditions preferably include: a temperature of 80 to 100°C and a time of 24h.
[0059] The present invention also provides a resin catalyst prepared by the preparation method described in the above technical solution, wherein the resin catalyst has active groups, and the active groups include sulfonate, perfluoroalkylsulfonyl and mercaptoalkylamine.
[0060] The present invention also provides application of the resin catalyst described in the above technical solution in the synthesis of bisphenol A.
[0061] In the present invention, the application preferably comprises the following steps:
[0062] 1) mixing the resin catalyst with phenol and swelling them to obtain a swollen product;
[0063] The mass ratio of the resin catalyst volume to phenol is 5 mL:40 g;
[0064] The swelling conditions include: stirring at 70° C. for 3 h;
[0065] 2) mixing the swollen product obtained in step 1) with acetone and reacting the mixture to obtain bisphenol A;
[0066] The mass ratio of acetone to phenol is 2.5:40;
[0067] The reaction conditions include: temperature of 70° C. and reaction time of 4 h.
[0068] In the present invention, the application preferably comprises the following steps:
[0069] The resin catalyst was loaded into a stainless steel fixed bed reactor, and the phenol-acetone mixture was heated at 70°C at a space velocity of 1 h -1 Carry out continuous reaction to obtain bisphenol A;
[0070] The stainless steel fixed bed reactor has an inner diameter of 30 mm and a length of 200 mm;
[0071] The residence time of the phenol-acetone mixture in the catalyst bed of the stainless steel fixed bed reactor is 1 hour;
[0072] The molar ratio of phenol to acetone in the phenol-acetone mixed solution is 10:1.
[0073] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0074] The yield and selectivity calculation method of bisphenol A produced by the reaction of phenol and acetone is as follows:
[0075] Yield Y(%) = C BPA (94.11×R+58.08) / 228.28×100···(1) where C BPA is the content of bisphenol A in the reaction solution; 94.11 is the molecular weight of phenol; R is the molar ratio of phenol to acetone in the raw material; 58.08 is the molecular weight of acetone; 228.28 is the molecular weight of bisphenol A.
[0076] Selectivity S(%) = C BPA / (C BPA +C 色满 +C 2,4-双酚A +C 三酚 +C 其他 )···(2)In the formula, C BPA , C 色满 , C 2,4-双酚A , C 三酚 , C 其他 , are the contents of bisphenol A, chroman, 2,4-bisphenol A, triphenol and other impurities in the reaction solution respectively.
[0077] Example 1
[0078] Preparation of catalyst:
[0079] In a 1000mL four-necked flask, add 100g macroporous cross-linked polystyrene microspheres (average particle size: 850μm, average pore size: 55nm, cross-linking degree: 10%), 500mL dichloroethane, swell for 40min, then add 600g fuming sulfuric acid and 200g trifluoromethanesulfonic acid respectively, heat to 90℃, stir at 300rpm for 12h. The product is washed with ethanol and deionized water to neutrality to obtain a modified resin;
[0080] In a 2000mL four-necked flask, add 1000mL deionized water, 100g modified resin, and 5.49g N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt. Under inert gas protection and at a temperature of 80°C, stir at 300rpm for 8h. Wash the product with deionized water until it is neutral, and vacuum dry it at a temperature of 80°C for 24h to obtain resin catalyst A.
[0081] Example 2
[0082] As in Example 1, 200 g of trifluoromethanesulfonic acid was replaced with 266 g of pentafluoroethanesulfonic acid to obtain resin catalyst B.
[0083] Example 3
[0084] As in Example 1, 200 g of trifluoromethanesulfonic acid was replaced with 333 g of perfluoropropanesulfonic acid to obtain resin catalyst C.
[0085] Example 4
[0086] As in Example 1, 200 g of trifluoromethanesulfonic acid was replaced with 400 g of perfluorobutanesulfonic acid to obtain resin catalyst D.
[0087] Comparative Example 1
[0088] The same process as in Example 1 was performed except that no trifluoromethanesulfonic acid was added to obtain resin catalyst E.
[0089] Comparative Example 2
[0090] Resin catalyst F was obtained as in Example 1 except that trifluoromethanesulfonic acid and N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt were not added.
[0091] Example 5
[0092] 2g of each resin catalyst A, B, C, D, E, and F were measured, ground into powder using a mortar, and then pressed into tablets using a tablet press. The thickness of the tablets was about 0.5mm. Subsequently, at room temperature, the contact angle of deionized water dropped on the surface of the sheet sample was measured using a contact angle meter at multiple different locations on the sample surface. The average value was calculated to obtain the static contact angle data of the sample. The results are shown in Figure 2 .from Figure 2 It can be concluded that the grafting of perfluoroalkylsulfonyl groups onto the resin can make the resin more hydrophobic, and as the number of carbon atoms in the perfluoroalkylsulfonyl group increases, the hydrophobicity becomes better.
[0093] Example 6
[0094] Into a 250ml four-necked flask equipped with a 100℃ thermometer and a stirring paddle and dried and anhydrous, 5ml of dried resin catalyst A, B, C, D or E and 40g of phenol were added respectively, and the reactor was sealed. The four-necked flask was placed in a 70℃ constant temperature water bath and stirred for 3 hours to allow the catalyst to fully swell. 2.5g of accurately weighed acetone was sucked into each reaction bottle with a syringe and quickly injected into each reaction bottle. After reacting at 70℃ for 4 hours, samples were taken and the contents of each component in the reaction liquid were determined by gas phase analysis. The yield and selectivity of bisphenol A were calculated according to formulas (1) and (2). The results are shown in Table 1.
[0095] Table 1 Comparison of the activity of resin catalysts
[0096]
[0097]
[0098] Example 7
[0099] 100 g of resin catalyst C was loaded into a stainless steel fixed bed reactor with an inner diameter of 30 mm and a length of 200 mm. A phenol-acetone mixture (the molar ratio of phenol to acetone in the phenol-acetone mixture was 10:1) was heated at 70 °C at a space velocity of 1 h. -1 The reaction was continuous, and the residence time of the phenol-acetone mixture in the catalyst bed of the stainless steel fixed bed reactor was 1 h. The reaction products were collected at the reactor outlet, and the contents of the components in the reaction solution were determined by gas phase analysis. The yield and selectivity of bisphenol A were calculated according to formulas (1) and (2). Figure 3 .from Figure 3 It can be concluded that the catalyst activity and selectivity remained basically unchanged when the resin catalyst C was loaded into a fixed bed reactor to catalyze the synthesis of bisphenol A for 120 consecutive days, showing excellent stability.
[0100] Comparative Example 2
[0101] As in Example 7, resin catalyst C was replaced with resin catalyst E, and a phenol-acetone mixture (the molar ratio of phenol to acetone in the phenol-acetone mixture was 10:1) was heated at 70°C at a space velocity of 1 h -1 The reaction was continued, and the reaction products were collected at the reactor outlet. The contents of the components in the reaction solution were determined by gas phase analysis, and the yield and selectivity of bisphenol A were calculated according to formulas (1) and (2). Figure 4 .from Figure 4 It can be concluded that when resin catalyst E is loaded into a fixed bed reactor to catalyze the synthesis of bisphenol A, the activity of the resin catalyst begins to slowly decrease after about 20 days. After 120 days of operation, the BPA yield drops from 83% to 64%. Compared with resin catalyst C, its stability is poor.
[0102] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a resin catalyst, characterized in that: The following steps are involved: 1) swelling the macroporous cross-linked polystyrene microspheres to obtain swollen microspheres; 2) mixing the swollen microspheres obtained in step 1) with fuming sulfuric acid and a sulfonic acid reagent and stirring the mixture to react to obtain a modified resin; The sulfonic acid reagent includes one or more of trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, perfluoropropanesulfonic acid and perfluorobutanesulfonic acid; 3) Mixing the modified resin obtained in step 2) with N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt, and performing heat treatment under the protection of an inert gas to obtain a resin catalyst.
2. The preparation method according to claim 1, characterized in that: In the step 1), the particle size of the macroporous cross-linked polystyrene microspheres is 800-1000 μm, the pore size is 50-100 nm, and the cross-linking degree is 10-20%; The swelling conditions include: mixing the macroporous cross-linked polystyrene microspheres with ethylene dichloride and swelling for 40 minutes; The mass ratio of the macroporous cross-linked polystyrene microspheres to the volume ratio of ethylene dichloride is 100 g:500 mL.
3. The preparation method according to claim 1, characterized in that: In the step 2), the mass ratio of fuming sulfuric acid, sulfonic acid reagent and macroporous cross-linked polystyrene microspheres is 6:2:
1.
4. The preparation method according to claim 1, characterized in that: The stirring reaction conditions in step 2) include: temperature of 90° C., time of 12 h, and rotation speed of 300 rpm.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the modified resin in step 3) to the N,N,N-trimethyl-3-mercaptopropyl quaternary ammonium salt is 100:5.
49.
6. The preparation method according to claim 1, characterized in that: The heat treatment conditions in step 3) include: temperature of 80° C., time of 8 h, and rotation speed of 300 rpm; After the heat treatment, the resin catalyst is obtained by washing and drying in sequence; Wash with deionized water until neutral; The drying conditions include: a temperature of 80-100° C. and a drying time of 24 hours.
7. A resin catalyst prepared by the preparation method according to any one of claims 1 to 6, wherein the resin catalyst has active groups, and the active groups include sulfonate, perfluoroalkylsulfonyl and mercaptoalkylamine.
8. Use of the resin catalyst according to claim 7 in the synthesis of bisphenol A.
9. The use according to claim 8, characterized in that: The application comprises the following steps: 1) mixing the resin catalyst with phenol and swelling them to obtain a swollen product; The mass ratio of the resin catalyst volume to phenol is 5 mL:40 g; The swelling conditions include: stirring at 70° C. for 3 h; 2) mixing the swollen product obtained in step 1) with acetone and reacting the mixture to obtain bisphenol A; The mass ratio of acetone to phenol is 2.5:40; The reaction conditions include: temperature of 70° C. and reaction time of 4 h.
10. The use according to claim 8, characterized in that: The application comprises the following steps: The resin catalyst was loaded into a stainless steel fixed bed reactor, and the phenol-acetone mixture was heated at 70°C at a space velocity of 1 h -1 Carry out continuous reaction to obtain bisphenol A; The stainless steel fixed bed reactor has an inner diameter of 30 mm and a length of 200 mm; The residence time of the phenol-acetone mixture in the catalyst bed of the stainless steel fixed bed reactor is 1 hour; The molar ratio of phenol to acetone in the phenol-acetone mixed solution is 10:1.